RESEARCH METHODS OF FOOD MARKETING (International Journal of Innovative Technologies in Economy, 2022)
As a result, the main purpose of choosing marketing research methods is to get acquainted with different methods that can be used in the collection and analysis of marketing information. In practice, they are conventionally divided into traditional and specific methods. Traditional methods of analysis include methods and techniques that have been used since the advent of economic analysis and are widely used in data processing and analysis in other areas: the system of analytical indicators, factor modeling, comparison and grouping methods, etc.